Trends in Sports Marketing - Čáslavová, Eva, et, al (Karolinum, 2025)
The book Trends in Sports Marketing explores the evolution of sports marketing, focusing on current and emerging trends that shape the industry. The book covers the integration of digital elements, such as social media, online advertising, and e-commerce, as well as successful online marketing strategies like content creation and fan engagement. It also examines the role of sports celebrities in promoting brands and events. The final chapter highlights innovations in sports services and customer participation. This insightful publication offers valuable knowledge for professionals and enthusiasts navigating the ever-changing sports marketing landscape.
Keywords: Marketing a reklama